Aerology, Part 1D. Upper Wind (Maudheim, 71 degrees 03'S, 10 degrees 56 'W) - Robin,G. De Q.; Hisdal,V. (1970)
Upper winds were measured by Rawin (SCR658) using a separate unmodulated 400 mc transmitter attached to the sounding balloon. The first ascent was made on 15 March 1950, and daily ascents commenced on 1 April 1950 and continued until 10 January 1952, when 626 upper wind measurements had been completed. A much better idea of the air circulation over the Antarctic has been gained from the investigations carried out during the IGY and in the following years. (Author)